(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article describes the status of our national musical heritage, the attention paid to our school of performing arts, the special decisions made by our state, and the qualifications of students in sarokhbori Dugoh 2-3 singing. Methodical recommendations on singing sarakhbori Arcs 2-3 Tarot cards are given.